Cross-sectional comparison of age- and gender-related comorbidities in people living with HIV in Canada. Issue 28 (15th July 2022) - Brunetta, Jason M.; Baril, Jean-Guy; de Wet, Joseph J.; Fraser, Chris; Rubin, Gary; Thomas, Réjean; Loemba, Hugues; Logue, Ken; Silverman, Michael; Palmart, Jean; Jiang, Haiyan; Lorgeoux, René-Pierre; et al.
Abstract : Because antiretroviral therapy (ART) is allowing people living with human immunodeficiency virus (PLWH) to survive longer, they are developing more age-related comorbidities. We evaluated the effects of age and gender on the burden of age-related comorbidities among PLWH. In this retrospective real-world study, de-identified data were extracted from the medical charts of 2000 HIV-positive adults on ART across 10 sites in Canada. The prevalence of age-related comorbidities was determined in 6 age subgroups (<30, 30–39, 40–49, 50–59, 60–69, and ≥70 years). The effects of gender on these comorbidities were also examined. Risks of cardiovascular disease and chronic kidney disease (CKD) were calculated using the Framingham and D:A:D equations. Most persons were White (68%), male (87%), and virologically suppressed (94%). The mean age was 50.3 years (57% aged ≥50 years), and mean CD4 + T-cell count was 616 cells/mm 3 . The most common comorbidities were neuropsychiatric symptoms (61%), overweight/obesity (43%), liver disease (37%), and dyslipidemia (37%). The mean number of comorbidities increased across age subgroups ( P < .001). Across all age subgroups, the prevalence of hypertension ( P = .04), dyslipidemia ( P = .04), CKD ( P = .03), bone fragility ( P = .03), and depression ( P = .02) differed between males and females. Both age ( P < .001) and gender ( P < .001) impacted cardiovascular disease and CKD risk. Age and gender influenced the burden, types, and risks of age-related comorbidities in PLWH in this Canadian cohort. These comorbidities should be diagnosed and treated in routine clinical practice.